Electricity-to-ammonia interconversion in protonic ceramic cells: advances, challenges and perspectives - Liang, M.; Kim, J.; Xu, Xiaomin; Sun, H.; Song, Y.; Jeon, S.H.; Shin, T.H.; Shao, Zongping; Jung, W.C. (2025)
NH3 is an attractive alternative fuel to hydrogen and methane, offering advantages such as easy compression at room temperature, straightforward storage and transportation, high volumetric energy density, and carbon-free nature. However, conventional NH3 synthesis requires high temperatures and pressures, resulting in substantial energy consumption and increased equipment and maintenance costs. Protonic ceramic cells (PCCs), as a cutting-edge energy conversion technology, can realize NH3 synthesis at moderate pressures and low-to-intermediate temperatures by utilizing surplus renewable electricity generated by wind and solar power. Additionally, PCCs can be employed to convert NH3 into electricity to meet instantaneous demand, providing a means to address the seasonal and intermittent nature of renewable energy sources. Despite their potential, the commercial application of electricity-to-NH3 interconversion in PCCs faces several challenges, primarily related to insufficient performance and durability. This review systematically explores the mechanisms and challenges of electricity-to-NH3 interconversion in PCCs, highlights recent advancements in NH3 synthesis using PCCs and direct NH3-fueled proton ceramic fuel cells (DA-PCFCs), and discusses perspectives for realizing high-efficiency electricity-to-NH3 interconversion. This review aims to establish a scientific foundation for efficient electricity-to-NH3 interconversion via PCCs and provides critical insights for designing high-performance and durable PCC components.